Mitochondria–lysosome crosstalk in GBA1-associated Parkinson’s disease - Sahyadri, M.; Nadiga, Abhishek P. R.; Mehdi, Seema; Mruthunjaya, K.; Nayak, Pawan G.; Parihar, Vipan K.; Manjula, S. N. (3 Biotech, 2022)
Organelle crosstalk is significant in regulating their respective functions and subsequent cell fate. Mitochondria and lysosomes are amongst the essential organelles in maintaining cellular homeostasis. Mitochondria–lysosome connections, which may develop dynamically in the human neurons, have been identified as sites of bidirectional communication. Aberrancies are often associated with neurodegenerative disorders like Parkinson's disease (PD), suggesting the physical and functional link between these two organelles. PD is often linked with genetic mutations of several mutations discovered in the familial forms of the disease; some are considered risk factors. Many of these genes are either associated with mitochondrial function or belong to endo-lysosomal pathways. The recent investigations have indicated that neurons with mutant glucosylceramidase beta (GBA1) exhibit extended mitochondria–lysosome connections in individuals with PD. This may be due to impaired control of the untethering protein, which aids in the hydrolysis of Rab7 GTP required for contact untethering. A GCase modulator may be used to augment the reduced GBA1 lysosomal enzyme activity in the neurons of PD patients. This review focuses on how GBA1 mutation in PD is interlinked with mitochondria–lysosome (ML) crosstalk, exploring the pathways governing these interactions and mechanistically comprehending the mitochondrial and lysosomal miscommunication in the pathophysiology of PD. This review is based on the limited literature available on the topic and hence may be subject to bias in its views. Our estimates may be conservative and limited due to the lack of studies under the said discipline due to its inherent complex nature. The current association of GBA1 to PD pathogenesis is based on the limited scope of study and further research is necessary to explore the risk factors further and identify the relationship with more detail.